Food safety and health: a survey of rural and urban household consumer practices, knowledge to food safety and food related illnesses in Ogun State (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Consumers’ knowledge on food safety and related practices play central role in reducing foodborne diseases, which represents significant concerns to public health.Objectives: To evaluate rural and urban household consumers knowledge of food safety and related practices in Ogun state, Nigeria. Also, awareness of foodborne illnesses, and  association between respondents’ demographic characteristics and food safety knowledge were investigated.Methods: A crossectional study, which involved a questionnaire based interview of a group of 120 volunteers from four different local government areas (LGA) in Ogun State was conducted. Pearson chi-square analysis was used to test the association between consumers’ demographic parameters and knowledge of food safety.Results: Overall,  eighteen (15.8%, 95% Cl, 10.0 – 23.7) male, and ninety-six (82.2%, 95% Cl, 76.3 – 89.9) female within the age range 16 – 60 years took part in the study. Our data showed that there was poor knowledge regarding food safety practices and food borne illnesses among rural and urban consumers surveyed. However, there was a significant difference in the awareness of rural and urban household consumers to foodborne illnesses and associated complications, (p